Hubungan Antara Tingkat Pengetahuan dan Sikap Masyarakat dengan Kepatuhan Penggunaan Masker Selama Pandemi Covid-19 - Rinna Merlin Sorongan; Novie Homenta Rampengan; Ralph Kairupan; Oksfriani Jufri Sumampouw (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: The multidimensional impact of the Covid-19 pandemic has the potential to hamper regional development. Therefore, it is necessary to know the level of community compliance in the use of masks as an application of health protocols in Amurang District. The purpose of this study was to analyze the correlation between the level of knowledge and public attitudes with compliance with the use of masks during the Covid-19 pandemic in Amurang District, South Minahasa Regency. Method: This is a correlational study. This research was carried out in Amurang District, South Minahasa in May 2022. The respondents of this study were the community, amounting to 95 people. The variables in this study were the level of knowledge, attitudes and compliance with the use of masks. The instrument used is a questionnaire. Bivariate data analysis. Results: The results showed that as many as 81 respondents have a positive attitude towards the use of masks and 73 people (90.1%) of them have a level of compliance in the use of masks. The results of this study indicate that as many as 81 respondents have a positive attitude towards the use of masks and 73 people (90.1%) of them have a level of compliance in the use of masks. The results of statistical tests found that there was no significant relationship between attitudes towards the use of masks and community compliance in the use of masks, where the p value was 0.108 (p>0.05).. Conclusion: It can be concluded that there are the correlation between the level of knowledge and compliance with the use of masks in the community in Amurang District, South Minahasa.